The relative food value of different milling products as indicated by their percentage of nitrogen - Clothier, R. W. (My University, 1897)
Introduction: Since this thesis will deal largely with the relative food value of different brands of flour made from the same wheat, a short discussion of the process of manufacturing flour will be in order before taking up in detail the results obtained by chemical analysis. Nearly all of the flour in the United States is now manufactured by what is known as the “gradual reduction process.” In this process the wheat berry passes through several distinct stages of reduction before it is completely reduced to flour. The reduction is accomplished by means of rollers and each stage of the reduction is technically termed a “break”. Before the reduction process begins the wheat must be thoroughly cleansed from all foreign matter such as weed seeds, dirt, pieces of iron, etc. This is accomplished by means of various machines. Metallic bodies are removed by passing the wheat in a stream over large magnets. Adhering dirt is removed by means of scouring and brush machines, while foreign seeds may be removed by means of screens. In some cases the wheat is also passed through a set of “ending stones” which remove the fug from the end of the berry. After the wheat has thus been cleaned it is passed through corrugated rollers set so as to just split the berry along the crease.
Citation: Clothier, R. W. The relative food value of different milling products as indicated by their percentage of nitrogen. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Flour; Milling; Wheat; Machinery; Agriculture; Grain science; Theses; Manuscripts (documents)